2019
DOI: 10.2147/ndt.s237116
|View full text |Cite
|
Sign up to set email alerts
|

<p>MicroRNA-Based Biomarkers in the Diagnosis and Monitoring of Therapeutic Response in Patients with Depression</p>

Abstract: Depression is a debilitating mental illness that affects up to 120 million people worldwide; it is currently determined based on subjective diagnostic schemes that are limited by high uncertainty. Hence, there is an urgent need to identify effective and reliable biomarkers to increase diagnostic accuracy. MicroRNAs (miRNAs) constitute a recently discovered class of non-coding RNAs that play a key role in the regulation of gene expression by modulating translation, messenger RNA (mRNA) degradation, or stability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 98 publications
0
21
0
1
Order By: Relevance
“… 33 , 34 MiRNAs have been proven to be used for the diagnosis and treatment biomarkers of depression. 35 , 36 Here, we found that Berberine could regulate miR-34b-5p, miR-470-5p and BDNF expression, so we speculated that Berberine regulated the progression of depression disorder through miRNA/mRNA axis. Around this hypothesis, a series of experiments were carried out.…”
Section: Discussionmentioning
confidence: 75%
“… 33 , 34 MiRNAs have been proven to be used for the diagnosis and treatment biomarkers of depression. 35 , 36 Here, we found that Berberine could regulate miR-34b-5p, miR-470-5p and BDNF expression, so we speculated that Berberine regulated the progression of depression disorder through miRNA/mRNA axis. Around this hypothesis, a series of experiments were carried out.…”
Section: Discussionmentioning
confidence: 75%
“…Although collection of CSF is not as easy as collection of blood, it is thought to better represent fluctuations in miRNAs status than peripheral tissue or even post-mortem brain samples [ 158 , 159 ]. Its close interaction with the brain makes CSF an ideal candidate for study changes in the CNS [ 160 , 161 ].…”
Section: Mirnamentioning
confidence: 99%
“…Since miRNA concentration can rapidly change in order to compensate for changes in environment [ 164 ], they seem to be perfect candidates for such markers [ 165 ]. Indeed, a great body of evidence was provided by clinical, preclinical and in vitro studies showing that changes of miRNA expression can reflect the progress of depression treatment ( Table 5 ) [ 159 ].…”
Section: Mirnamentioning
confidence: 99%
“…Even if the body of evidence in relation to miRNAs and HNC prognosis is growing, there is wide variability among studies regarding aims, miRNA measurement methods, tumor sites and different miRNAs among studies [ 1 ]; in fact, miRNA can be detected in both extracellular and intracellular environments. In addition, consistency between many miRNA signatures is lacking, and the differences may be due to source of miRNA, sample size and comorbidities of the studied samples [ 8 ]. Recently, in order to address the significance of miRNAs as potential prognosticators in HNC, some articles [ 1 , 9 ] studied the impact of miRNA by identifying the pooled effect size across all HNC prognostic studies, resulting in a summary estimates of the relationship between miRNAs expression and risk of death via pooling the hazard ratio across all selected studies with the aim of providing a better understanding of the survival outcome of HNC patients.…”
Section: Introductionmentioning
confidence: 99%